Public Spectacles, Private Narratives:: Canadian Heritage Campaigns, Maternal Trauma and the Rise of the Koffort (trunk) in Icelandic-Canadian Popular Memory - Bertram, Laurie (Material Culture Review, 2010)
Abstract The late rise of the previously undervalued migrant trunk, or "koffort" within Icelandic-Canadian popular culture is easily linked to the proliferation of migration-focused visual heritage campaigns in Canada from 1967 onwards. This corresponding re-emergence in local art and museums, as well as in family homes, suggests that Icelandic-Canadians have simply adopted the static, celebratory image of migration history set forth by the state. However, by using interviews and photographs detailing the mnemonic uses of these objects in private, this article contends that the trunk is a hybrid object that offers families archives and points of contact for histories of trauma that also draw from traditional Icelandic notions of fatalism and matrilineal systems of identification. Despite its redemptive public image, the trunk is often the vehicle through which are revealed female-centred narratives of migrant trauma—spousal abuse, widowhood and infant mortality. Rather than delivering a cohesive vision of settler nationalism to Canadians, the migrant trunk has emerged as a powerful, but unsettling archive in popular practice.